Effect of Zeolite-Fe on Graphite Anode in Electroactive Biofilm Development for Application in Microbial Fuel Cells - Ureta-Zanartu, M (Elsevier B.V., 2019)
The performance of microbial fuel cells (MFCs) is highly dependent on the electrode materials. The electrode surface can be modified to provide a favorable environment for biofilms to enhance electron transfer from the bacteria to the anode. In this work, Faujasite zeolite-Y (ZY) was exchanged with iron (Fe) and was used to modify glassy carbon/graphite electrodes (GC/gr-ZY Fe ) evaluating its effect in electroactive biofilm development for application in microbial fuel cells. The novel material was evaluated as an anode in MFCs by comparing its performance with GC/gr and GC/gr-ZY electrodes. The results show that when using a GC/gr-ZY Fe electrode, an electroactive biofilm with good electrochemical activity for acetate degradation can be generated on the electrode surface. The maximum current density obtained with a GC/gr-ZY Fe -BF electrode (where BF is biofilm) was 7.7 times higher than that of a GC/gr anode. The modification generates a less hydrophobic electrode surface that facilitates microbial cell attachment, thereby improving bioelectricity production. By using scanning electron microscopy, a homogeneous microbial community with bacteria that had a similar short rod-shaped morphology was observed. Furthermore, electrochemical impedance spectroscopy demonstrated that the charge transfer resistance (R ct ) decreased as the biofilm grew, revealing that the presence of the biofilm facilitated the electrochemical reaction. After 7 days of MFC operation, the GC/gr-ZY Fe bioanode showed a reduction in R ct from 212.9 ± 1.81 Ω to 151.5 ± 1.46 Ω which was 2.4 times lower than that achieved with GC/gr. The biofilm on GC/gr-ZY Fe was characterized using cyclic voltammetry, and the results showed a larger oxidation peak (169.8 μA cm −2 ) than that of the GC/gr electrode (36.5μA cm −2 ), further supporting the better electron-transfer properties of the modified electrode. Additionally, this result confirms the capability of biofilms to act as bioelectrocatalysts under acetate-oxidizing conditions. © 2018 Elsevier B.V.